Retrospective cohort mortality study of workers at an aircraft maintenance facility. II. Exposures and their assessment. Issue 8 (August 1991) - Stewart, P A; Lee, J S; Marano, D E; Spirtas, R; Forbes, C D; Blair, A
Abstract : Methods are presented that were used for assessing exposures in a cohort mortality study of 15, 000 employees who held 150, 000 jobs at an Air Force base from 1939 to 1982. Standardisation of the word order and spelling of the job titles identified 43, 000 unique job title organisation combinations. Walkthrough surveys were conducted, long term employees were interviewed, and available industrial hygiene data were collected to evaluate historic exposures. Because of difficulties linking air monitoring data and use of specific chemicals to the departments identified in the work histories, position descriptions were used to identify the tasks in each job. From knowledge of the tasks and the chemicals used in those tasks the presence or absence of 23 chemicals or groups of chemicals were designated for each job organisation combination. Also, estimates of levels of exposure were made for trichloroethylene and for mixed solvents, a category comprising several solvents including trichloroethylene, Stoddard solvent, carbon tetrachloride, JP4 gasoline, freon, alcohols, 1, 1, 1-trichloroethane, acetone, toluene, methyl ethyl ketone, methylene chloride, o-dichlorobenzene, perchloroethylene, chloroform, styrene, and xylene.